The implementation of SDG12 in and from higher education institutions: universities as laboratories for generating sustainable cities - Martínez-Acosta, Mariajulia; Vázquez-Villegas, Patricia; Mejía-Manzano, Luis Alberto; Soto-Inzunza, Gladis Valeria; Ruiz-Aguilar, Karina Mayela; Kuhn Cuellar, Luis; Caratozzolo, Patricia; Membrillo-Hernández, Jorge (Frontiers in Sustainable Cities, 2023)
Introduction It is known that the world is facing and will face significant sustainability challenges. Sustainable Development Goal 12 (SDG12), responsible consumption and production, is one of the most relevant SDGs for building Sustainable Cities. This study is based on the analysis of the implementation of SDG12 in cities, starting from universities as laboratories or first examples of sustainability. Methods The study was carried out through a multilevel scale approach. A systematic review of the literature (global scale) of the last 5 years (2018–2022) was conducted. An analysis of the program and the initiatives of a Higher Education Institution (Tecnologico de Monterrey) is presented (local scale). Finally, a survey was applied to Faculty at this University (micro-scale). Results The systematic review indicated that the main themes or aspects addressed in SDG12 by higher education institutions were sustainable food, supply chains, community, infrastructure, technology, policies, energy consumption, the collaborative economy, smart cities, and curricula. The local scale analysis highlighted the Distrito Tec project, 37 institutional initiatives, and 26 courses directly related to SDG12. The survey showed that 8% of Faculty considered SDG12 the most important of the SDGs and stated that this goal is necessary to reduce environmental impacts. As the most significant impact that Universities can have on SDG12, 52% of the Faculty consider that Universities should become living labs in the transition toward sustainable cities, followed by 36% who think it would be better to implement operational facilities. Discussion The diverse contributions of the HEIs at the three scales were classified into six categories: culture, mitigation, adaptation, education, research, and outreach. The study indicates that SDG 12 has been achieved by universities in different ways, which overlaps widely with the performance of other SDGs. Results demonstrate that following a multistakeholder approach, international collaborations between HEIs can foster technology-driven multi-disciplinary research projects to consolidate sustainable cities. Building capacity to accelerate the transition of universities into urban living labs will promote climate action among the students who enroll every year.